(untitled) (Challenges of the Future, 2024)
Research Question (RQ): What is the impact of food marketing and advertising on childhood obesity? Purpose: The purpose of this research is to analyze the existing regulatory measures and legislation on food marketing aimed at children, understand its effects and look for ways to reduce childhood obesity. Method: This research was conducted through analysis and comparison of the current legislation and regulatory measures on food marketing enforced in Brazil, Chile and the United States. As well as, consulting multiple scientific articles on the research subject. Results: Regulations, such as the ones implemented in Chile, have shown to be effective when it comes to limiting the exposure of children to persuasive and manipulative food marketing. Consequently, causing a significant decrease in children’s consumption of such food products, which, in turn, can lead to the decrease in childhood obesity. Organization: This research can help governments and organizations find effective measures to create, improve as well as enforce legislation and regulations on child-oriented food marketing. Society: People are susceptible to the influence and manipulation of persuasive marketing strategies. Thus, children, being the more easily influenced part of the population, are even more vulnerable to such tactics. This research paper helps further showcase this fact as well as the dangers posed by these marketing strategies, subsequently proposing options to counteract the impact of said damaging tactics. Originality: Unlike most others of its kind, this research brings a comparative approach when analyzing the effectiveness of regulations in Latin American countries and the United States when it comes to the marketing of ultra-processed food products directed at children. Limitations / further research: Limitations faced were the lack of primary research sources and lack of in-depth research sources in this specific topic. Further research could expand the subject countries to include other Latin American countries, as well as European and Middle Eastern countries. Keywords: Child-oriented marketing, Nutrition, Law, Regulations, Food Advertisement, Childhood Obesity, Food Labeling, Comparative Law.